An Interdisciplinary and Intersectoral Action-research Method: Case-Study of Climate Change Adaptation by Cities Using Participatory Web 2.0 Urban Design - VACHON, Geneviève; Chouinard, Marie-Noí«l; Cloutier, Geneviève; Dubois, Catherine; Després, Carole (Enquiry The ARCC Journal for Architectural Research, 2013)
This paper discusses the last segment of a three-year interdisciplinary and intersectoral action research on climate change and urban transformation. The project had, as one of its core missions, the role of imagining urban and architectural adaptations for urban neighbourhoods that would contribute to minimizing the negative impacts of climate change on people’s comfort, health and safety. The first part of the paper describes the collaborative design and augmented participation method used in the context of Québec City, Canada. These include the design process conducted to imagine adaptation scenarios, the visual strategies undertaken to make these understandable for the population, and the Web 2.0 crowdsourcing approach forwarded to measure feasibility and social acceptability of the design and visualization strategies. The second part discusses three positive outcomes of the process. First, collaborative design conducted with intersectoral groups of experts constitutes a promising avenue to identify adaptations and evaluate their relevance. Second, crowdsourcing is a powerful tool to inform the general public about climate change including both negative and potential aspects. As well, the crowdsource model allows access to particular knowledge which empowered users to make changes around their homes and neighbourhoods or advocating action from their local government. Crowdsourcing is also an efficient tool to help understand what people know about the potential impact of climate change and how it bears on their comfort, health and safety. Third and finally, the design proposals and the evaluation comments generated by working closely with various stakeholders, along with the public on-line consultation, allow for the induction of pragmatic recommendations that can be used as decision aids by elected officials and civil servants to better prepare their municipalities for climate change.